Question and answer
Question not found
Ask a question
Not a good answer? Get an answer now. (Free)
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
Find the equation (-4,-1) (3,-3) graph.Arrange your answer in the form y = mx + b, where b is the constant.
Weegy: please refer below [ link ] (More)
Question
Expert Answered
Updated 7/11/2013 1:27:00 PM
2 Answers/Comments
(-4,-1) (3,-3), the equation in y = mx + b form is
y = -2/7x - 15/7.
The formula is m = y2 - y1/x2 - x1.
Added 7/11/2013 1:26:20 PM
This answer has been added to the Weegy Knowledgebase
If you can't answer the question, just pass it to another expert. Referring users to other websites without answering the question directly is not allowed as stated on the rules.

Added 7/11/2013 1:27:00 PM
t Object]User: Arrange your answer in the form y = mx + b, where b is the constant. (0, 0) m = 2
Weegy: (0, 0) m = 2, the equation of the line in the form y = mx + b is y = 2x User: (im asking this question again because weegy showed to me object obejcet can u answer again thanks) Arrange your answer in the form y = mx + b, where b is the constant. (2, 1) m = 0 Weegy: (2, 1) m = 0, the equation is y = 1 User: Arrange your answer in the form y = mx + b, where b is the constant. (1, 3) m = 3 Weegy: (1, 3) m = 3, the equation of the line is y = 3x. User: Arrange your answer in the form y = mx + b, where b is the constant. (-1, 0) m = -2 Weegy: (-1, 0) m = -2, the equation is y = -2x - 2 (More)
Question
Expert Answered
Asked 7/11/2013 1:15:15 PM
0 Answers/Comments
Arrange your answer in the form y = mx + b, where b is the constant. (-1, 0) m = -2
Question
Not Answered
Updated 112 days ago|7/1/2014 11:55:51 AM
1 Answer/Comment
where b is the constant. (-1, 0) m = -2

y = mx + b
0 = (-2)(–1) + b
0 = 2 + b
-b = 2
b = -2

the equation of the line is
y = -2x - 2
Added 112 days ago|7/1/2014 11:55:51 AM
This answer has been confirmed as correct, not copied, and helpful.
Arrange your answer in the form y = mx + b, where b is the constant. (-1, 0) m = -2
Weegy: The equation for (-1,0) m = -2 is y = -2x - 2 User: help more? Weegy: I believe you are the same person earlier. The conversation was gone right after I sent my last answer. Sorry about that. User: yeah im same i don't know what happend Arrange your answer in the form y = mx + b, where b is the constant. (-6, 1) m = 6 Weegy: (-6,1) m = 6, the equation is y = 6x + 37 User: Arrange your answer in the form y = mx + b, where b is the constant. (1, 3) m = 2 (More)
Question
Expert Answered
Asked 7/11/2013 1:57:40 PM
0 Answers/Comments
Arrange your answer in the form y = mx + b, where b is the constant. (1, 3) m = 2
Weegy: The equation of a line given the point and slope is: m=2 y = 2x + b because m = 2 y = mx + b y = 2x + b 3 = 2(1) + b y = 2x + 1 User: so where is the answer ? (More)
Question
Expert Answered
Asked 7/11/2013 2:08:25 PM
0 Answers/Comments
17,919,615 questions answered
Popular Conversations
what is micro
Weegy: A microorganism is a microscopic organism, which may be a single cell or multicellular organism. User: what ...
10/21/2014 7:38:45 PM| 3 Answers
Solve the inequality. 2(4 + x) > 4(x + 4) A. x > 4 B. x > ...
Weegy: 2w + 3 > 14; 2w > 14 - 3; 2w > 11; w > 11/2 User: Solve the inequality. 5a + 12 6 B. a < 6 C. D.
10/21/2014 12:59:56 PM| 3 Answers
Anime
10/21/2014 9:41:19 AM| 2 Answers
what are quadratic equations
Weegy: You can apply quadratic equation to cook marshmallows by following these steps: 1. Select a quadratic ...
10/21/2014 10:48:49 AM| 2 Answers
What is the solution set of 2x ^2 - 3x = 5?
10/21/2014 11:05:05 AM| 2 Answers
Simplify -(-2a + 13) + (-9a - 2) - (-7a - 3).
Weegy: -(-2a + 13) + (-9a - 2) - (-7a - 3) = (-7a - 15) - (-7a - 3) = -12
10/21/2014 11:12:50 AM| 2 Answers
Determine the solution set of (x + 1)2 = 25. {-8, 6} {-8, ...
Weegy: The answer is 77,520. There are 77,520 possible committees that can be formed.
10/21/2014 11:18:30 AM| 2 Answers
Simplify (x - y + 1) - (x + y - 1).
Weegy: (x - 4)(x + 3) = x^2 + 3x - 4x - 12 = x^2 - x - 12
10/21/2014 11:19:54 AM| 2 Answers
Solve the inequality 4x User: x + 1/2 < 1/4
10/21/2014 11:27:18 AM| 2 Answers
Simplify p(p - q) - q(q - p).
Weegy: 3 - (2 - 8) = 3 - (-6) = 3 + 6; = 9
10/21/2014 11:46:35 AM| 2 Answers
Social welfare User: stigma
10/21/2014 12:28:06 PM| 2 Answers
Weegy Stuff
S
L
1
1
1
1
L
1
L
Points 2267 [Total 14642]| Ratings 0| Comments 2267| Invitations 0|Offline
S
L
1
L
P
C
1
P
C
1
L
Points 1464 [Total 10945]| Ratings 3| Comments 1434| Invitations 0|Offline
S
1
L
1
L
P
P
L
Points 781 [Total 13010]| Ratings 0| Comments 781| Invitations 0|Offline
S
L
Points 487 [Total 1886]| Ratings 0| Comments 487| Invitations 0|Offline
S
Points 479 [Total 479]| Ratings 0| Comments 449| Invitations 3|Offline
S
1
L
L
Points 474 [Total 6268]| Ratings 3| Comments 444| Invitations 0|Offline
S
Points 352 [Total 353]| Ratings 4| Comments 312| Invitations 0|Offline
S
Points 207 [Total 207]| Ratings 1| Comments 197| Invitations 0|Offline
S
P
C
L
P
L
1
Points 48 [Total 6282]| Ratings 0| Comments 48| Invitations 0|Offline
S
Points 27 [Total 27]| Ratings 0| Comments 27| Invitations 0|Offline
Home | Contact | Blog | About | Terms | Privacy | Social | ©2014 Purple Inc.